Decomposition of the Zenga inequality index I(Y) into the contributions of macroregions and income components – an application to data from Poland and Italy - Zenga, Michele; Jędrzejczak, Alina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The total income Y can be expressed as the sum of c components called income sources. The N units of the population can be partitioned into k different subpopulations. In the paper the decompositions by subpopulations as well as by income components of the point ()hIY and the synthetic ()IY inequality indexes proposed by Zenga in 2007 are considered. These indexes can be decomposed into the contributions of income sources and/or into the contributions of subpopulations ,and also the decomposition into within- and between-group inequality can be carried out. In the paper, the two-step approach was used: first of all “additive” decompositions of the point index were derived, and then, by averaging these decompositions, the corresponding decompositions of the synthetic index were obtained. The results were then applied to the analysis of income distributions in Poland and Italy based on the household budget surveys conducted by Statistics Poland and the Bank of Italy, respectively
Argumenta Oeconomica, 2020, Nr 1 (44), s. 101-125